The Implementation of Cambridge Curriculum in the Excellent Class of MTsN 3 Jombang - Shobikah, Nanik; Syafri, Mohamad; Sofia, Iva; Mahsus, Mahsus; Rahmawati, Fitria; Maisaroh, Ummi; Yuni, Prima Novia (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
English Language Learning in Excellent Class of MTsN 3 Jombang is integrated with the Cambridge Curriculum and it is one of the leading programs in MTsN 3 Jombang to Go International. This qualitative descriptive research used purposive sampling techniques. The subjects in this study were the Head of the Madrasah, the Vice of curriculum, the Head of the Excellent Class Program, and the English Teacher Excellent Class. Data collection is carried out by carrying out observations, interviews, and documentation. Data analysis is carried out by data reduction, data display, and conclusions. The validity of the data is checked by triangulation and member check. The findings in this article are 1) Learning Planning aims to prepare learners to compete at local, national, and international levels; 2) Learning implementation is carried out intensively for 3 months in Grades VII-IX to equip students and develop optimally English using the Cambridge Curriculum; and 3) Learning Evaluation consists of written tests, oral tests, and practice tests.